Countering terrorist financing: the practicioner's point of view - Pieth, Mark; Thelesklaf, Daniel; Ivory, Radha (Lang, 2009)
Terrorists need money to commit acts of violence and sustain their operations. Measures to combat terrorism therefore aim to prevent terrorists from raising, moving and using funds or other assets. The effectiveness "Giessbach" seminar on counter-terrorist financing (CTF) organised by the Basel Institute on Governance in October 2008. This book contains essays presented at the seminar written by practiitioners and academics with extensive experience in the field of CTF. The authors offer a diversity of views on the domestic, regional and international initiatives aimed at detecting terrorist funds in the financial system, preventing terrorists from moving their money via alternative financial channels and facilitating the recovery of terrorist assets. The editors conclude with insights into the ongoing challenge of making CTF measures both effective and legally sustainable in the lead-up to Giessbach III in December 2009.